Analysis of the flow induced by the undulatory fin motion of seahorse - Botello Payro, Emanuela; Rauh, Cornelia; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.analys

Biocompatible visualization of flow fields generated by microorganisms - Zima-Kulisiewicz, Bogumila Ewelina; Botello Payro, Emanuela; Delgado, Antonio (Notes on Numerical Fluid Mechanics and Multidisciplinary Design. Imaging Measurement Methods for Flow Analysis, 2009)
Microflow induced by the ciliates called Opercularia asymmetrica is an interesting phenomenon in biofluidmechanics. Ciliates play an important role in the structural formation of microbial granules derived from activated sludge. Additionally, flow induced by protozoa (ciliates) is treated as an efficient mean of nutrient transport with minimum energy requirement. For the first time powerful digital imaging techniques are used for studying microorganismic convection. Investigations of the flow generated by Opercularia asymmetrica are carried out with help of digital micro Particle Image Velocimetry. Digital micro Particle Tracking Velocimetry is implemented to analyse cilia motion. In biological fluid mechanics flow visualization techniques must guarantee biocompatibility. Thus, in the present work appropriate light illumination and suitable seeding particles are used. Moreover, in order to predict artefacts and correct them novel neuronumerical hybrid is employed. © 2009 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2009.tech.ITC.stmmec.biocom

Biokompatible Visualisierung von Mikroströmungen und der ciliaren Bewegung von opercularia asymmetrica mittels mikro particle image velocimetry und mikro particle tracking velocimetry - Botello Payro, Emanuela; Zima-Kulisiewicz, Bogumila Ewelina; Rauh, Cornelia; Delgado, Antonio (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.biokom

Kinematics and hydrodynamics of undulatory fin motion of seahorse - Zima-Kulisiewicz, Bogumila Ewelina; Lienhart, Hermann; Rauh, Cornelia; Delgado, Antonio; Botello Payro, Emanuela; Krupczynski, Philipp; Schuster, Stefan (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.kinema